Model-Based Testing of Object-Oriented Reactive Systems with Spec Explorer - Veanes, Margus; Campbell, Colin; Grieskamp, Wolfgang; Schulte, Wolfram; Tillmann, Nikolai; Nachmanson, Lev (Formal Methods and Testing, 2008)
Testing is one of the costliest aspects of commercial software development. Model-based testing is a promising approach addressing these deficits. At Microsoft, model-based testing technology developed by the Foundations of Software Engineering group in Microsoft Research has been used since 2003. The second generation of this tool set, Spec Explorer, deployed in 2004, is now used on a daily basis by Microsoft product groups for testing operating system components, .NET framework components and other areas. This chapter provides a comprehensive survey of the concepts of the tool and their foundations.
The attached file is a preliminary version.